Aesthetic Rehabilitation of Enamel Hypomineralization with Microabrasion and Direct Composites (18 Month-Follow-up Report) - KORKUT, BORA; TOPBAŞI, FAİK BÜLENT; YILMAZ ATALI, PINAR (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: This case report represents a direct, prepless treatment of discolored anterior teeth due to Molar-Incisor Hypomineralisation (MIH) defect following microabrasion and vital bleaching. Methods: Following clinical and radiological examinations, the discolored, teeth were microabraded with a microabrasive agent containing 6.6% HCI (hydrochloric acid) and silicone carbide particles. Then the teeth were bleached by using 40% hydrogen peroxide. Finally direct composite restorations were performed with A2 shade. Polishing procedure was done by using polishing discs and spiral wheels. Result: The restorations were evaluated in terms of retention, marginal integrity, marginal discoloration, anatomical form, secondary caries, surface texture, shade match, and postoperative sensitivity according to 'The Modified United States Public Health Service' (USPHS) criterias at 3rd, 9th and 18th months. Nevertheless, it was detected slight abrasion at 18-month follow-up on the labial surfaces of teeth #11 and #21, all the scores were considered as acceptable. Conclusion: The microabrasion, vital bleaching and direct composite restoration combination is considered as a promising treatment method for MIH effected teeth under the conditions of this study.
Keywords: Microabrasion; Direct Composite; Bleaching; MIH; Aesthetic dentistry; MOLAR INCISOR HYPOMINERALIZATION; SURFACE-ROUGHNESS; ETIOLOGIC FACTORS; RESIN; PREVALENCE; OPACITIES; MIH